Émergence insoumise: réflexions sur la persistance du racisme systémique envers les femmes autochtones - Wylde, Cyndy (Harangues, 2024)
« Émergence insoumise s'ouvre sur un souvenir de l'autrice qui attend un taxi après un colloque : « Non, mais croyez-vous vraiment que moi, une femme des Premières Nations, je vais aller attendre seule le soir, à Val-d'Or? » Ces mots, adressés au gardien qui lui indique que les portes de l'université sont sur le point de fermer, seront le catalyseur d'une réflexion sur le sort réservé aux femmes autochtones, aussi bien dans le milieu carcéral que dans la société canadienne en général. Alternant entre les réminiscences personnelles et les analyses du racisme systémique afin d'aller au-delà des statistiques et des préjugés, cet essai de Cyndy Wylde s'inscrit dans une tradition de littérature de combat, qui bouscule les idées reçues et dynamite le confort et l'indifférence. »
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; discours dominant; féminisme autochtone; phi4336; philosophie; premier cycle; privilèges; périodes historiques; québec; racisme; racisme systémique; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

Le féminisme décolonial en Abya Yala - Curiel, Ochy; De Roo, Priscilla (Multitudes, 2021)
Les rapports sociaux de race, de genre, de sexe sont inextricablement mêlés : telle est une idée centrale du féminisme décolonial tel qu’il se déploie depuis Abya Yala, du nom que le peuple kuna donnait au continent américain. L’article situe l’importance de renommer les femmes et féministes d’origine autochtone, une manière de défaire les discours coloniaux (parfois tenus par des universitaires féministes) sur les pratiques de genre avant la colonialité/modernité. Ochy Curiel illustre cette idée à partir de l’expérience du GLEFAS (Groupe latino-américain de formation et d’action féministe) : le décolonial n’y est pas seulement une critique du savoir académique, il est profondément ancré dans des pratiques autogestionnaires de luttes anticapitalistes, dans le lesbianisme politique, dans la rue, dans les associations, dans les organisations communautaires.
Keywords: amériques; anthropologie; anthropologie sociale; approches et analyses; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; intersectionnalité; lesbianisme; militance; pol4212; premier cycle; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Femmes autochtones et militantisme en ligne: usages de Facebook et Twitter pour contrer les violences sexuelles dans la foulee du scandale policier de Val-d'Or - Pilote, Anne-Marie; Hubner, Lena A. (Recherches Feministes, 2019)
Les auteures interrogent l’apport des médias socionumériques aux luttes des femmes autochtones du Québec. À la suite du scandale de Val-d’Or – qui a vu des agents de la Sûreté du Québec éclaboussés par des allégations d’agressions sexuelles envers des femmes des nations crie et anichinabée –, les chercheuses ont mené une observation ethnographique dans les comptes Facebook et Twitter des principales militantes et associations autochtones ayant investi les médias socionumériques pour dénoncer ces violences policières. Complétée par des entrevues, leur analyse montre que la variété des actions privilégiées en ligne donne une visibilité accrue aux luttes des femmes autochtones et favorise leur prise de parole. Ces actions se révèlent des moyens efficaces pour décoloniser l’ordre social patriarcal et forger un « espace de la cause des femmes autochtones ».
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; communication; cours; discipline; féminisme autochtone; militance; pol4105; premier cycle; périodes historiques; québec; racisme; régions géographiques; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; val-d'or; violences; violences policières; violences sexuelles

Living on the land: indigenous women's understanding of place - Altamirano-Jiménez, Isabel; Kermoal, Nathalie J.; Horn-Miller, Kahente (AU Press, 2016)
From a variety of methodological perspectives, contributors to Living on the Land explore the nature and scope of Indigenous women's knowledge, its rootedness in relationships, both human and spiritual, and its inseparability from land and landscape.
Keywords: amériques; approches et analyses; canada; cours; cree; discipline; environnement; féminisme autochtone; histoire; métis; naskapi; nicaragua; pol4105; premier cycle; ressource en ligne; régions géographiques; sciences humaines; thématiques; études autochtones; île de la tortue

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Nānīawig Māmawe Nīnawind. Debout et solidaires. Femmes autochtones disparues ou assassinées au Québec - Québec, Femmes autochtones au; Bergeron, Annie; Boileau, Alana; Lévesque, Carole (Femmes autotchtones au Québec, 2015)
Le présent document fait état des résultats d’une enquête exploratoire effectuée par Femmes Autochtones au Québec (FAQ) en ce qui a trait à la situation des femmes autochtones disparues ou assassinées au Québec. Cette enquête a bénéficié du soutien financier du ministère de la Justice du Québec et du Réseau de recherche et de connaissances relatives aux peuples autochtones (DIALOG). Elle visait principalement à consigner et à mettre en valeur la parole des Autochtones de différents horizons et provenances, de même que celles des membres des familles de femmes autochtones disparues ou assassinées, principales personnes concernées par la problématique.
Keywords: amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; justice sociale; pol4105; premier cycle; québec; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Lessons in Self-Defense: Gender Violence, Racial Criminalization, and Anticarceral Feminism - Thuma, Emily (Women's Studies Quarterly, 2015)
Keywords: 1900-1999; 1980-1989; afro-féminisme; amériques; antiracisme; approches et analyses; cours; discipline; féminisme autochtone; féminismes noirs; histoire; injustice; intersectionnalité; militance; patriarcat; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; résistance; sciences humaines; systèmes d'oppressions; thématiques; viol; violences; violences d'état; violences sexistes et sexuelles; états-unis; études de genres

Land as pedagogy: Nishnaabeg intelligence and rebellious transformation - Simpson, Leanne Betasamosake (Decolonization: Indigeneity, Education & Society, 2014)
A resurgence of Indigenous political cultures, governances and nation-building requires generations of Indigenous peoples to grow up intimately and strongly connected to our homelands, immersed in our languages and spiritualities, and embodying our traditions of agency, leadership, decision-making and diplomacy. This requires a radical break from state education systems – systems that are primarily designed to produce communities of individuals willing to uphold settler colonialism. This paper uses Nishnaabeg stories to advocate for a reclamation of land as pedagogy, both as process and context for Nishnaabeg intelligence, in order to nurture a generation of Indigenous peoples that have the skills, knowledge and values to rebuild our nation according to the word views and values of Nishnaabeg culture.
Keywords: amériques; approches et analyses; canada; cours; discipline; environnement; féminisme autochtone; histoire et politique; nishnaabeg; pol4105; premier cycle; premières nations; pédagogie; pédagogie nishnaabeg; régions géographiques; résistance; résurgence; savoirs autochtones; sciences de l'éducation; sciences humaines; sociologie; système colonial; systèmes d'oppressions; systèmes éducatifs; territoire nishnaabeg; thématiques; éducation par le territoire

Plan Nord - Où sont les femmes autochtones ? - Arnaud, Aurélie (Recherches amérindiennes au Québec, 2011)
Parmi les sujets absents du débat sur les impacts et les conséquences du Plan Nord se trouvent, invisibles, les femmes autochtones. Celles qui constituent plus de 50 % de la population autochtone dans le Nord sont les moins écoutées, les moins consultées, les plus vulnérables. La question est absente et il y a peu de données disponibles quant à l’impact des activités minières ou des chantiers hydroélectriques sur la condition des femmes. Or, l’expérience de Femmes autochtones du Québec révèle que ce type de développement a souvent des incidences négatives sur la situation des femmes autochtones dans les communautés en exacerbant les préjugés, les violences et les inégalités. Pour poser la réalité des femmes autochtones dans et hors réserve, il faut préciser qu’en 2001, les femmes autochtones enregistraient un taux de monoparentalité deux fois plus élevé que celui des femmes non autochtones (19 % contre 8 %). Les nombreuses familles dirigées par des femmes autochtones sont donc plus dépendantes de l’aide sociale que les hommes autochtones le sont.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; inégalités; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Un protocole d'application culturellement pertinent selon les sexes - Association des femmes autochtones du Canada (AFAC) (2011)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; pol4105; premier cycle; périodes historiques; québec; régions géographiques; santé; santé mentale; sciences humaines; sciences sociales; suicide; système colonial; systèmes d'oppressions; thématiques; traumatismes générationnels; travail social; violences

La grand-maternité chez les Inuits Portrait d’une réalité méconnue - Sigouin, Catherine; Charpentier, Michèle; Quéniart, Anne (Nouvelles pratiques sociales, 2011)
Cet article explore la grand-maternité telle qu’elle est construite et vécue chez les Inuits du Nunavik, à partir d’une recension de la littérature ainsi que des résultats préliminaires d’une recherche qualitative visant à connaître le point de vue des grands-mères inuites sur leur place et leurs rôles au sein de la famille. L’étude met notamment en lumière la place centrale et indispensable des grands-mères dans les soins et l’éducation des petits-enfants. Elle soulève également certains questionnements quant à la pertinence des programmes psychosociaux actuellement en place. Ces observations tendent en faveur d’une reconnaissance du rôle essentiel des grands-mères inuites à travers la mise en place de programmes et de services mieux adaptés à cette clientèle.
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; féminisme autochtone; féminisme décolonial; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; travail social; trs1205

Dancing on our turtle's back: Stories of Nishnaabeg re-creation, resurgence, and a new emergence - Simpson, Leanne (ARP Books, 2011)
Many promote Reconciliation as a "new" way for Canada to relate to Indigenous Peoples. In Dancing on Our Turtle's Back: Stories of Nishnaabeg Re-Creation, Resurgence, and a New Emergence activist, editor, and educator Leanne Simpson asserts reconciliation must be grounded in political resurgence and must support the regeneration of Indigenous languages, oral cultures, and traditions of governance. Simpson explores philosophies and pathways of regeneration, resurgence, and a new emergence through the Nishnaabeg language, Creation Stories, walks with Elders and children, celebrations and protests, and meditations on these experiences. She stresses the importance of illuminating Indigenous intellectual traditions to transform their relationship to the Canadian state. Challenging and original, Dancing on Our Turtle's Back provides a valuable new perspective on the struggles of Indigenous Peoples.
Keywords: amériques; approches et analyses; autochtones; canada; com5170; cours; cycles supérieurs; discipline; fem1000; fem3600; fem7000; féminisme autochtone; féminisme décolonial; linguistique; lit2815; lit3220; politique; premier cycle; réconciliation; régions géographiques; sciences humaines

Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's Native and northern series, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques

Itinéraires d'égalités. Trajectoires des femmes autochtones du Québec et du Canada - Levesque, Carole; Labrecque, Marie France (30e anniversaire de l’Association des Femmes Autochtones du Québec, 2007)
À l’occasion du 30e anniversaire de l’Association des Femmes autochtones du Québec, ces actes de colloque proposent de revoir le parcours des femmes autochtones dans leurs luttes pour l’égalité et la justice sociale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; environnement; féminisme autochtone; histoire et politique; inégalités; justice sociale; mexique; militance; pol4105; premier cycle; pédagogie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones

In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Introduction to "Indigenous Women: The State of Our Nations."(Canada)(Editorial) - Lawrence, Bonita; Anderson, Kim (Atlantis, 2005)
Introduction to the issue 29, 2 "Indigenous Women: The State of Our Nations".
Keywords: approches et analyses; cours; discipline; féminisme autochtone; histoire et politique; pol4105; premier cycle; sciences humaines; sciences sociales; thématiques

Namaji: Two-Spirit Organizing in Montreal, Canada - Meyer-Cook, Fiona; Labelle, Diane (Journal of Gay & Lesbian Social Services, 2004)
This article traces the authors' involvement in Two-Spirit organizing in Montreal since 1995. The term Two-Spirit is often used by lesbian, gay, bisexual and transgendered (LGBT) people of Aboriginal descent in both the U.S. and Canada. The authors explore the multifaceted aspects of organizing within a Two-Spirit community. They begin with an examination of contemporary challenges facing Two- Spirit people within Canadian society and then provide several concrete examples of local organizing, ranging from the creation of an educational video on HIV/AIDS and participation in a collaborative project with a school of social work to national and international alliance-building.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; militance; montréal; personnes bispirituelles; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2014; thématiques; travail social; études gaies et lesbiennes

Suzanne MacKenzie Memorial Lecture conceptually unclad: feminist geography and Aboriginal peoples * - Peters, Evelyn J. (The Canadian Geographer, 2004)
This paper argues that feminist geography can provide some useful lessons in an attempt to increase Aboriginal peoples' representation in geography. It asks the question: How can we use the example of feminist geography to think about a geography that is more inclusive of Aboriginal people? The paper focuses on the issues of content in teaching, drawing on examples from urban and social geography, and on methodological challenges, especially the issue of reflexivity. Feminist geographer Suzanne Mackenzie argued that an emerging feminist geography left the discipline ‘conceptually unclad’, challenging scholars to consider new theoretical frameworks and new perspectives. I argue that emphasising the geographies of Aboriginal people also enriches geography, including feminist geography.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; démographie; environnement; féminisme autochtone; géographie; géographie féministe; géographie urbaine; histoire et politique; méthodologie; pol4105; premier cycle; périodes historiques; sciences humaines; thématiques

La forêt vive: récits fondateurs du peuple innu - Savard, Rémi (Boréal, 2004)
Le volume présente et commente quatre récits de la création du monde enregistrés en langue innu par l'auteur, anthropologue réputé, à l'été 1970, sur la Basse-Côte-Nord. La parenté entre ces récits et les diverses cosmologies eurasiennes est soulignée en conclusion. [SDM].
Keywords: amériques; anthropologie; approches et analyses; canada; cours; culture autochtone; culture innu; discipline; féminisme autochtone; histoire et politique; labrador; nation innue; nitassinan; pol4105; premier cycle; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques

The fourth world: an indigenous perspective on feminism and aboriginal women's activism - Ouellette, Grace Josephine Mildred Wuttunee (Basics from Fernwood Publishing, 2002)
"This book is not about feminism. Rather, feminism is the basis of the discussion, an example of how understanding oppression must consider a number of barriers. Euro-Canadian feminists rarely address the circumstances that are unique to First Nations' women, instead working with the assumption that all women are a part of a similar struggle. Ouellette attempts to confront these barriers. Throughout interviews with a number of women, she highlights the following four questions. To what extent do Aboriginal women understand experience and articulate their oppression? To what extent do colonized women perceive racism as the source of their oppression? To what extent do Aboriginal women view male domination within their own Aboriginal societies as the source of the oppression? How do Aboriginal women articulate racism and gender oppression?The author argues that there will always be a dichotomy between European and Aboriginal thought. This book makes an important contribution toward a greater understanding of Aboriginal thought and an Aboriginal perspective on society. The Fourth World theory is an integrate part of the "Circle of Life" philosophy of Aboriginal people. In keeping with oral traditions, these teachings are passed on at gatherings and in private conversations. They compromise a distinctly Aboriginal worldview."
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones

Les femmes des Premières nations, la gouvernance et la loi sur les Indiens : recueil de rapports de recherche en matière de politique - Sayers, Judith F.; MacDonald, Kelly A.; Fiske, Jo-Anne; Newell, Melonie; George, Evelyn; Cornet, Wendy (2001)
Table de matières: Pour une participation équitable des femmes des Premières nations à la gestion des affaires publiques, Judith F. Sayers et Kelly A. MacDonald. Les femmes des Premières nations et la gouvernance : Étude sur les coutumes et les nouvelles pratiques chez les femmes de la Première nation de Lake Babine, Jo-Anne Fiske, Melonie Newell et Evelyn George. La gouvernance des Premières nations, la Loi sur les Indiens et les droits à l’égalité des femmes, Wendy Cornet.
Keywords: amériques; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; inégalités; militance; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme

I am woman: A native perspective on sociology and feminism - Maracle, Lee (Press Gang, an imprint of Raincoast Books, 1996)
Je suis une femme représente ma lutte personnelle contre la féminité, la culture, les croyances spirituelles traditionnelles et la souveraineté politique, écrite à une époque où cette lutte n'était pas terminée. Mon intention initiale était de donner aux femmes autochtones les moyens de prendre à cœur leur propre lutte personnelle pour être féministe autochtone. Les modifications apportées à cette deuxième édition du texte ne modifient pas mon intention initiale. Cela reste ma tentative de présenter la perspective sociologique d'une femme autochtone sur les impacts du colonialisme sur nous, en tant que femmes, et sur moi personnellement.
Keywords: amériques; approches et analyses; canada; cours; discipline; fem1300; féminisme autochtone; pol4105; premier cycle; régions géographiques; sciences humaines; sociologie

The Traditional Roles of Native Women in Canada and the Impact of Colonization - Brodribb, Somer (The Canadian Journal of Native Studies, 1984)
Recent trends in feminist research indicate a growing interest in the impact of Native women on westward expansion and imperialism. The author suggests that while early European contacts affected the status of women negatively, the views of Native women were seldom recorded during these early contact periods. Recent studies have examined the status and changing roles of Native women from the viewpoints of contemporary Native women. The diversity of their opinions continues to be a part of the contemporary debate on the resilience and resourcefulness of Native women in the past.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 1970-1979; 1980-1989; amériques; approches et analyses; canada; cours; discipline; famille; féminisme autochtone; histoire et politique; intersectionnalité; mariage; pol4105; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; sociologie; sofia; système colonial; systèmes d'oppressions; thématiques; violences